Human Rights Protection in Business Practices: Between Social Responsibility and Legal Compliance - Winsherly Tan; Wan Rosalili Wan Rosli; Yudhi Priyo Amboro; Mimi Sintia Mohd Bajury; Elizabeth Gunawan (Lex Publica, 2025)
This study examines human rights protection in business practices in Indonesia, emphasizing the role of corporations in respecting, protecting, and redressing the rights of workers and communities. Although Indonesia has ratified international instruments such as the ICESCR and enacted sectoral laws such as Law No. 13 of 2003 concerning Manpower, Law No. 32 of 2009 concerning Environmental Protection, and the Job Creation Law, human rights violations remain rampant, including substandard wages, suppression of labor unions, violations of indigenous peoples' rights, and limited access to redress mechanisms. Using a normative-empirical approach, this study analyzes national laws and international standards through descriptive analysis. The findings indicate that wage and worker welfare policies serve as important indicators of respect for human rights, while corporate practices often prioritize economic efficiency over ethical obligations. This study underscores the urgent need to integrate the UN Guiding Principles on Business and Human Rights into Indonesia's legal framework.